Knowledge, Attitude, and Practice regarding Anaphylaxis among Pediatric Health Care Providers in a Teaching Hospital - Patnaik, Sibabratta; Krishna, Samarth; Jain, Mukesh Kumar (Journal of Child Science, 2020)
Anaphylaxis is a severe, life threatening generalized or systemic hypersensitivity reaction which requires prompt, accurate diagnosis, and appropriate management. The objective of the study is to assess the extent of knowledge, management skills, and attitude on anaphylaxis among pediatric health care providers of a tertiary care teaching hospital. This was a cross-sectional study done in the department of pediatrics, which included faculty, residents, interns, and nurses. The knowledge, attitude, and practice were assessed using a standardized questionnaire comprised of 35 questions. The questionnaire was distributed and collected in person to all the participants. Informed consent was obtained from all participants and confidentiality was ensured at all stages. Collected data were analyzed using SPSS version 20. The mean of total knowledge score (TKS) was 7.36 ± 1.42. TKS of faculty was 8.36 ± 1.15, in residents 7.81 ± 1.25, in interns 7.46 ± 1.15, and in nurses 6.69 ± 1.57. Knowledge scores of faculty, residents, and interns were significantly higher than that of nurses while there was no significant difference between faculty, residents, and interns. The majority of participants have positive attitude toward anaphylaxis. Incorrect practice is followed by most of the participants. The extent of knowledge about anaphylaxis among pediatric health care providers is moderate but management skills remains suboptimal. Thus, proper training, through continued medical educations and programs to improve abilities to recognize and manage anaphylaxis are very crucial. Differential approach may be followed to different groups; nurses need extra training for optimal management of anaphylaxis.
Keywords: allergy; epinephrine; glucocorticoid; TKS